Sweet taste does not modulate pain perception in adult humans - Mooney, ER; Davies, AJ; Pickering, AE (F1000Research, 2020)
Background: Sugar is routinely used to comfort neonates undergoing painful procedures, and animal studies have shown that sucrose increases the time to withdrawal from painful stimuli. However, there are no published studies examining the effects of sweet substances on heat pain thresholds and percept in adult humans.